Harmony and Moderation in Multireligious Society: Study of Interfaith Coexistence in Cigugur, Kuningan, West Java - Syahid, Ahmad Habibi; Ade Jaya Suryani; Katriani Puspita Ayu; Masykur (Indonesian Journal of Islamic Religious Education, 2025)
Indonesia is known for its diversity of religions, cultures, and ethnicities. Despite this diversity, peaceful and harmonious coexistence remains difficult due to interfaith hatred. Therefore, tolerance and moderation are essential pillars in building a peaceful social life. This harmonious coexistence is evident in Cigugur, Kuningan, West Java. All live side by side and reside in this area. Some of them even live in the same family. Most of the previous research focused on inter-religious tolerance, only a few emphasized the influence of local values ​​and the role of religious leaders in fostering harmony in multi-religious societies. This study seeks to elucidate the manifestation of religious harmony and moderation in Cigugur, focusing on the influence of religious leaders and communal social practices. This qualitative study, employing interviews, observation, and documentation, revealed that religious leaders in Cigugur possess varied perspectives; however, they concur that tolerance, mutual respect, and the appreciation of differences constitute the foundation of a peaceful existence. Interfaith dialogue, interfaith social activities, and local values ​​such as "Different Feelings, One Understanding" all contribute to a more harmonious society. This study demonstrates that harmony is not simply born from formal policies, but rather grows from cultural awareness and the behavior of religious leaders who can serve as role models, prioritizing humanity over differences.